The alliance-outcome association in borderline and obsessive-compulsive personality disorder - Beiling, Peter; Schurig, Susan; Keller, Andrea; Weidner, Kerstin; Noack, René (Frontiers in Psychiatry, 2023)
Personality disorders are considered a possible factor affecting the relationship between therapeutic alliance and therapy outcome. The present study investigated the alliance-outcome effect in patient groups with borderline personality disorder (BPD) and obsessive-compulsive personality disorder (OCPD). Data derived from a sample of n = 66 patients, treated in a day care hospital setting with a dialectical-behavioral and schema therapeutic treatment concept. Patients rated their symptom severity at admission, early alliance after 4-6 therapy sessions and symptom severity as well as alliance at discharge. Results showed no significant differences between BPD and OCPD patients regarding symptom severity and alliance. Multiple regression analyses indicated that the alliance was a significant predictor of symptom reduction, however only in the OCPD group. Our results showed an exceptionally strong alliance-outcome relationship in OCPD patients, suggesting that focusing on building a strong alliance and measuring it early in therapy may be especially beneficial for this patient group. For patients with BPD, a more regular screening of the therapeutic alliance might be helpful.